2014
DOI: 10.1016/j.stem.2013.12.013
|View full text |Cite|
|
Sign up to set email alerts
|

Secretion of Shh by a Neurovascular Bundle Niche Supports Mesenchymal Stem Cell Homeostasis in the Adult Mouse Incisor

Abstract: Mesenchymal stem cells (MSCs) are typically defined by their in vitro characteristics, and as a consequence the in vivo identity of MSCs and their niches are poorly understood. To address this issue, we used lineage tracing in a mouse incisor model and identified the neurovascular bundle (NVB) as an MSC niche. We found that NVB sensory nerves secrete Shh protein, which activates Gli1 expression in periarterial cells that contribute to all mesenchymal derivatives. These periarterial cells do not express classic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
424
3
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 377 publications
(465 citation statements)
references
References 65 publications
20
424
3
3
Order By: Relevance
“…SHH signaling was also recently shown to play an important role in the maintenance of dentin, the mesenchymal compartment of the incisor, which is located under the outer enamel surface (Zhao et al, 2014). The study showed that dentin turnover is dependent on HHresponding periarterial mesenchymal stem cells, which also contribute to dentin repair after injury.…”
Section: Teethmentioning
confidence: 89%
See 3 more Smart Citations
“…SHH signaling was also recently shown to play an important role in the maintenance of dentin, the mesenchymal compartment of the incisor, which is located under the outer enamel surface (Zhao et al, 2014). The study showed that dentin turnover is dependent on HHresponding periarterial mesenchymal stem cells, which also contribute to dentin repair after injury.…”
Section: Teethmentioning
confidence: 89%
“…The role of peripheral nerves in delivering signaling factors such as HH to regulate normal and regenerate non-neuronal tissues is only just beginning to emerge (Brownell et al, 2011;Zhao et al, 2014). Given this role of the nervous system in delivering HH ligands and the involvement of HH signaling in the developing enteric system (Liu and Ngan, 2013), it is interesting to speculate that HH released by nerves is also involved in transducing the signaling pathway in the GI system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, whether arteries, veins, and capillaries represent different MSC niches remains largely unknown. A recent study suggested that mouse incisor MSCs were localized around arterioles alone and not veins or capillaries and were regulated by the neurovascular bundle niche [38]. This finding may give a possible explanation as to why UCA-PSCs had a slight advantage over UCV-PSCs in terms of angiogenic capacity.…”
Section: Uca-pscs 3 Hmentioning
confidence: 94%